A fizetési meghagyás kibocsátása iránti kérelmek közjegyzői vizsgálata - Ferenczi, Fanni (Debreceni Jogi Műhely, 2015)
2010 marked the opening of a new chapter inthe more than 120 years history of the Hungarian order for payment procedure. Breaking with the Hungarian traditions, the notaries became competent to carry out these procedures instead of courts. The Hungarian Chamber of Civil Law Notaries established an accessible web-based computerised system for support of procedures. The registration of requests, the assignment of cases to notaries and the administrative handling of cases are carried out through this electronic network. The legislator’s aims when modified the regulation of this legal instrument was to reduce the duration of order for payment procedures and the workload of courts. In this paper I give an overview of the content of order for payment requests and of the practical experience of the notaries in connection with the examination of requests.